Epileptic seizures during Non-Ketotic Hyperglycemia (NKH) in French Guiana: A retrospective study - Baltyde, Dimitri; De Toffol, Bertrand; Nacher, Mathieu; Sabbah, Nadia (Frontiers in Endocrinology, 2022)
Introduction. Epileptic seizures during non-ketotic hyperglycemia (NKH) represent a rare complication of uncontrolled diabetes mellitus. The definition associates a blood sugar level > 200mg/dL (11mmol/L), hyperosmolality, absence of ketosis, dehydratation and seizure control after normalization of blood sugar levels. Material and methods. This retrospective observational study included patients hospitalized for epileptic seizures and NKH in the Cayenne Hospital Center between January 2010 and June 2020. The clinical, biological, and radiological results were collected. Results: 18 out of 228 (7.9%) patients with both diabetes and epileptic seizures had NKH. The mean age of the 12 women and 6 men was 64.8 years. In 8 patients, brain imaging did not show acute lesions and the seizures disappeared with control of hyperglycemia by hydration and insulin. In 6 patients, the seizures revealed a stroke, hemorrhagic in 4 cases, ischemic in 2 cases. 4 patients had a seizure in a context of known vascular epilepsy. The epileptic seizures were mainly focal seizures with motor symptoms that could be repeated, focal to bilateral tonic-clonic or focal status. Conclusion. Seizures in NKH are symptomatic of an acute brain lesion or vascular epilepsy more than 1 in 2 times. However, isolated NKH can cause seizures with a suggestive brain MRI. Keywords: diabetes, non-ketotic hyperglycemia, epileptic seizures, neuroendocrine entity, French Guiana.